2014
DOI: 10.3892/or.2014.3242
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor 7 enhances cell chemotaxis and migration of metastatic squamous cell carcinoma of head and neck through activation of matrix metalloproteinase-9

Abstract: The mechanisms leading to squamous cell carcinoma of head and neck (SCCHN) metastasis are not fully understood. Although evidence shows that the chemokine receptor 7 (CCR7) and its ligand CCL19 may regulate tumor dissemination, their role is not clearly defined in SCCHN. Matrix metalloproteinases break consisting of tissue barrier to the surrounding tissue invasion and metastasis by destroying the balance of matrix degradation of the basement membrane of tumor cells and extracellular matrix (ECM). We used chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Additionally, CCL21 is a potent stimuli for SCC migration [27]. Accordingly, CCL21 receptor -CCR7 -induces cytoskeleton modifications which in turn stimulate tumor cell migration, invasion, adhesion and survival of HNSCC cells via activation of PI3K/AKT and MAPK's and MMP-9 release [30,[32][33][34].…”
Section: Ccl19 and Ccl21mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CCL21 is a potent stimuli for SCC migration [27]. Accordingly, CCL21 receptor -CCR7 -induces cytoskeleton modifications which in turn stimulate tumor cell migration, invasion, adhesion and survival of HNSCC cells via activation of PI3K/AKT and MAPK's and MMP-9 release [30,[32][33][34].…”
Section: Ccl19 and Ccl21mentioning
confidence: 99%
“…In the context of oral cancer, it was previously shown that expression of CXCL8, CXCL6 (a CXCL8 homologue) and CXCR2 in tumor samples correlates with lymph node " CCL2 " ROS " proliferation, " invasion " tumor growth [19] HNSCC " invasion, " macrophage infiltration " angiogenesis [20] HNSCC and OSCC cell lines " CCL2 ; patient survival " CCL2 " ERK/AKT/STAT3 phosphorilation " survival in vitro [21] " CCL2 " EMT via AKT [ OSCC, and OSCC cell line " CCR7 " lymph node metastasis " stage " tumor size" CCL21/CCR7 " invasion " adhesion to lymph nodes in vitro [27] HNSCC, HNSCC cell lines and mice " CCL19 " lymph node metastasis CCR7 blockade ; AKT ; BCL-2 ; tumor growth [28] HNSCC and HNSCC cell lines " CCR7 " lymph node metastasis " adhesive ability [29] HNSCC and HNSCC cell lines " CCR7 " lymph node metastasis " CCR7 " migration " adhesion and cytoskeleton reorganization [30] " CCR7/CCL19 " PKCa " NF-KB " CCR7 " PKCa " stage " lymph node metastasis [31] " CCR7/CCL19 " PI3K " CDC42 and actin polymerization [32] " CCR7 " migration " MMP-9 " b1 integrin " cytoskeleton reorganization [33] " CCR7/CCL19 " ERK/JNK ; E-cadherin " vimentin " invasion [34] CCL20 (LARC, Exodus-1 and MIP3-a)…”
Section: Cxcl8mentioning
confidence: 99%
“…Chemokines, secreted by various cell types, play central roles in chemotaxis (5,6). According to the order of conserved cysteine residues, chemokines are classified into C, CC, CXC and C(X)3C, and CXC chemokines are further classified into ELR + CXC and ELR-CXC, according to the absence or presence of the amino-terminal ELR motif (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells with upregulated CCR7 disseminate from the primary tumor presumably by sensing the immobilized CCL21 gradient and actively migrate toward the next lymphatic vessel and the T-cell zone of lymph nodes. In addition to contributing to tumor cell survival by activating the phosphatidylinositol-3-kinase/Akt signaling pathway [29], the CCL21/CCR7 axis can upregulate matrix metalloproteinase 9 [30], E-cadherin, Slug, vimentin, and N-cadherin [31], which are considered as markers of epithelial-mesenchymal transition (EMT); that is to say, CCR7 can stimulate cancer cells to acquire an EMT phenotype. Accumulating evidence has shown that the EMT is a pathological process contributing to cancer progression, particularly cancer invasion, dissemination, and metastasis [32].…”
Section: Discussionmentioning
confidence: 99%